Indian Stock Market Efficiency Before and After the Introduction of Derivatives - Sekar, P.C.; Arasu, B.Senthil (Gyan Management Journal, 2007)
Market efficiency has influence on the investment strategy of an investor because if the market is efficient, trying to pick up under valued or over valued stocks will not be possible, because, in an efficient market there will be no undervalued or over valued stocks. This implies that stocks will not offer higher than deserved expected returns, given their risk. On the other hand if the market is not efficient, excess returns can be made by correctly picking the stocks. In this paper an analysis of stock indices of National Stock Exchange (NSE) is carried out to test the efficiency of Indian stock market and the randomness of stock price movement in the stock market using various tests.